Identification of roles for the SNARE-associated protein, SNAP29, in mouse platelets. (18th May 2016) - Williams, C.M.; Savage, J.S.; Harper, M.T.; Moore, S.F.; Hers, I.; Poole, A.W.
Abstract: Platelets are critical for maintaining vascular hemostasis, but also play a major role in the formation of occlusive cardiovascular and cerebrovascular thrombi under disease conditions. Secretion of platelet alpha and dense granules is a requirement for efficient thrombus formation. Understanding and targeting the mechanisms of secretion is important to aid the development of effective antithrombotics. SNAP29 is a tSNARE found in platelets, but whose role has not been defined. Using a platelet-specific SNAP29 knockout mouse model, we assessed the role of SNAP29 in platelet secretion and function under standardized conditions and also in in vitro and in vivo thrombosis. The data showed no major defects in SNAP29-null platelets, but revealed a minor defect in α-granule secretion and a significant increase in embolization rate of thrombi in vivo . These data suggest that SNAP29 contributes to the regulation of platelet α-granule secretion and thrombus stability, possibly partially masked by functional redundancy with other tSNAREs, such as SNAP23.